The Hyper-Kautz Network: A New Scalable Product Network. (2009) - Wei Wei, Wenhong Wenhong; Xiao Xiao, Wenjun Wenjun; Qin Qin, Yong Yong
Abstract : In this paper, we propose a new product network using a Cartesian product of hypercube and Kautz network, named as hyper-Kautz network. The proposed network possesses the properties of both hypercube and the Kautz network including logarithmic diameter, optimal connectivity, and simple routing algorithms.